Analisa Non-Linier Pada Mekanisme Keruntuhan Jembatan Rangka Baja Tipe Pratt - Istiono, Heri; Propika, Jaka (Jurusan Teknik Sipil, 2017)
Steel truss bridge collapse often occurs, both in Indonesia and in other countries. As a result of the collapse of the bridge is in addition to the casualties also losses from the financial aspects. This collapse caused due to various factors, one of them because of a decrease in the strength of the bridge structure. To minimize required maintenance of the bridge's collapse and to facilitate the maintenance of one of them must be known failure mechanisms existing bridges. In the analysis of this collapse, will be modeled steel truss bridge pratt’s type with long spans is 60 meters. Analysis of the collapse of the steel truss bridge's, utilizing a pushover analysis to analyze the behavior of the bridge structure. Pushover analysis done with give vertical static load pattern at the structure, next gradually increase by a factor until one vertical displacement target of the reference point is reached. The study shows that at model singe span failure occurred on the chord on mid span. The performance level of structure shows all models of bridges in the state are IO, this case based on the target displacement FEMA 356 and the actual ductility occurs in all models of bridges is compliant with SNI 2833-2008.